Relational depth from the perspective of the psychotherapy dyad: Psychometric properties of the Relational Depth Frequency Scale. (3rd October 2022) - Zarzycka, Beata; Jankowski, Tomasz; Szostek, Dorota; Di Malta, Gina; Cooper, Mick
Abstract: Objective: The Relational Depth Frequency Scale (RDFS) is a 6-item measure to assess the impact of relational depth experiences on psychotherapeutic outcomes. To date, the RDFS has only been validated in online samples of clinical and non-clinical individuals. This study aimed to examine the psychometric properties of the RDFS in clinical dyads of clients and psychotherapists. Method: A total of 86 psychotherapy dyads—86 psychotherapists (18 male, 68 female, mean age = 44.34) and 86 clients (17 male, 69 female, mean age = 34.22)—completed the RDFS, and the Scale to Assess the Psychotherapeutic Relationship (STAR), mid-psychotherapy. Results: CFA showed acceptable fit statistics for a one-factor model. The partial measurement invariance across both partners of the psychotherapeutic dyad was positively verified. The RDFS had good internal consistency for psychotherapists and clients ( α  = .90 and .81, respectively). Actor-partner interdependence model confirmed moderate to high levels of convergent validity against the STAR. Relational depth in both partners was predicted by their own perceptions of the quality of the psychotherapeutic relationship. Psychotherapist frequency of relational depth was also related to client perceptions of the psychotherapeutic relationship. Conclusion: The RDFS is a promising tool measuring relational depth both from psychotherapist and client perspectives.